Advances in accounting education teaching and curriculum innovations. Vol. 14 - Feldmann, Dorothy; Rupert, Timothy J. (Emerald, 2013)
Advances in accounting education : teaching and curriculum innovations publishes both non-empirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate. Topics included in Volume 14 are ways to increase student interest in the accounting major, challenges and implications associated with integrating transfer students into accounting programs, a techniques for improving performance in intermediate accounting classes, exercises for incorporating divergent and evolving standards in the audit class, guidance for incorporating the use of the tax code and regulations in introductory classes, and challenges educating the millennial generation offers to accounting educators.
Keywords: Accounting -- Study and teaching.; Finance -- Study and teaching.; elektronické knihy; electronic books